Effect of nickel catalyst layer thickness and grain size prepared by electroplating method to the growth of carbon nanostructures by chemical vapour deposition - Roszaini Md Salleh,; Yeoh, Wei Ming; Abdul Rahman Mohamed,; Raihana Bahru, (Penerbit Universiti Kebangsaan Malaysia, 2018)
A simple method of growing carbon nanostructures (CNS), a mixture of carbon nanotube (CNT) and carbon nanofiber (CNF), directly on a nickel catalyst layer electroplated on the copper substrate at low reaction temperature and atmospheric pressure via chemical vapor deposition (CVD) was investigated in this study. The nickel catalyst was prepared using electroplating methods and the current density was varied to give the nickel catalyst layer with different thicknesses and grain sizes prior to the growth of CNS which was carried out at 600°C and under a mixture of 25 sccm: 100 sccm of acetylene to nitrogen for 40 min. A nickel catalyst layer electroplated at 1 mA/cm2, which possess a smaller grain size and thinner layer of nickel catalyst, enables the synthesis of high quality and dense CNS as well as high ratio of CNT over CNF.